Piper sarmentosum Roxb. Attenuates Beta Amyloid (Aβ)-Induced Neurotoxicity Via the Inhibition of Amyloidogenesis and Tau Hyperphosphorylation in SH-SY5Y Cells - Chan, Elaine W.L.; Yeo, Emilia T.Y.; Wong, Kelly W.L.; See, Mun L.; Wong, Ka Y.; Yap, Jeremy K.Y.; Gan, Sook Y. (Current Alzheimer Research, 2021)
Background: In Alzheimer’s disease, accumulation of beta amyloid (Aβ) triggers amyloidogenesis and hyperphosphorylation of tau protein leading to neuronal cell death. Piper sarmentosum Roxb. (PS) is a traditional medicinal herb used by Malay to treat rheumatism, headache and boost memory. It possesses various biological effects, such as anti-cholinergic, anti-inflammatory, anti-oxidant and anti-depressant-like effects. Objective: The present study aimed to investigate neuroprotective properties of PS against Aβ-induced neurotoxicity and to evaluate its potential mechanism of action. Methods: Neuroprotective effects of hexane (HXN), dichloromethane (DCM), ethyl acetate (EA) and methanol (MEOH) extracts from leaves (L) and roots (R) of PS against Aβ-induced neurotoxicity were investigated in SH-SY5Y human neuroblastoma cells. Cells were pre-treated with PS for 24 h followed by 24 h of induction with Aβ. The neuroprotective effects of PS were studied using cell viability and cellular reactive oxygen species (ROS) assays. The levels of extracellular Aβ and tau proteins phosphorylated at threonine 231 (pT231) were determined. Gene and protein expressions were assessed using qRT-PCR analyses and western blot analyses, respectively. Results: Hexane extracts of PS (LHXN and RHXN) protected SH-SY5Y cells against Aβ-induced neurotoxicity, and decreased levels of extracellular Aβ and phosphorylated tau (pT231). Although extracts of PS inhibited Aβ-induced ROS production, it was unlikely that neuroprotective effects were simply due to the anti-oxidant capacity of PS. Further, mechanistic study suggested that the neuroprotective effects of PS might be due to its capability to regulate amyloidogenesis through the downregulation of BACE and APP. Conclusion: These findings suggest that hexane extracts of PS confer neuroprotection against Aβ- induced neurotoxicity in SH-SY5Y cells by attenuating amyloidogenesis and tau hyperphosphorylation. Due to its neuroprotective properties, PS might be a potential therapeutic agent for Alzheimer’s disease.
Keywords: Alzheimer' s disease